EPIDEMIOLOGY OF HYPERTENSION IN CROATIA (EHUH STUDY) -ECG FINDINGS AND CARDIOVASCULAR MORTALITY DATA AFTER 17 YEARS OF FOLLOW-UP. (June 2022) - Frkanec, Stjepan; Katic, Luka; Strbac, Tea; Tarnovski, Lorka; Boban, Marin; Sekulic, Mislav; Stojic, Vana; Trobonjaca, Adrian; Begic, Zvonimir; Barisic, Klara; Jelakovic, Ana; Blagus, Luka; et al.
Abstract : Objective: Our aim was to association of ECG findings and mortality data in random sample of Croatian population, an original cohort from the EHUH study after 17 years of follow up. Design and method: EHUH study is nation-wide survey on prevalence, treatment and control of hypertension in Croatia. In 2001–2003 a random sample of 1267 subjects were enrolled. Mortality data were analyzed after average period of 17 years. Office blood pressure (BP) was measured in sitting position using mercury sphygmomanometer three times at two visits and once at home visit: total 9 measurements -average BP values were calculated. Mortality data were collected from National Public Health Institute records. ECG scans were taken 17 years ago in 162 subjects and scans were analyzed by 2 different examiners manually, regardless one of another. In this group there were 17 deaths. Heart rate, intrinsic heart rate, RR interval, QT, TPe and QRS times, QTc and TPe/QTc ratios were analyzed across the groups. Results: Statistically significant differences were observed in distributions of intrinsic heart rate (p < 0.001) and QTc (p < 0.05) between subjects who died and survivors. Higher values of intrinsic heart rate were linked with lower mortality (B = -0.361, (p < 0.001). A smaller, but statistically significant difference was observed for QRS time (B = -0.045, p < 0.05) suggesting longer QRS times are linked with lower mortality. Conclusions: Our results which are not in line with other reports could be explained with small group, small number of events and most probably it is the case of reverse epidemiology.